URGENSI KOMUNIKASI LINTAS BUDAYA RUANG VIRTUAL DALAM SIARAN LANGSUNG YOUTUBE ALWAFATARIM - Wahyuni, Rufaidah Rika; Athoillah, Muhammad Reza; Jannah, Siti Raudahtul (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2025)
The development of digital technology has created virtual spaces that serve as primary arenas for intercultural communication in the era of globalization. This study aims to examine the urgency of intercultural communication within virtual spaces, specifically on the YouTube channel Alwafatarim TV, which actively presents religious and social-themed content. A qualitative research method is employed to analyze the interactions, narratives, and communication dynamics occurring on the channel. Data were collected through observation, interviews, and documentation. The results indicate that virtual spaces such as YouTube facilitate cultural exchange and broaden understanding among global communities. However, they also present challenges including differences in perception, stereotypes, and risks of misunderstandings due to diverse cultural backgrounds. Intercultural communication competence, digital literacy, and awareness of diversity are key factors in building harmonious and respectful interactions in virtual spaces. This study emphasizes the importance of adaptive and inclusive intercultural communication strategies so that digital platforms like Alwafatarim TV can positively contribute to strengthening tolerance and social integration in global society.